Intrauterine fetal demise: unravelling an obstetric enigma - N., Sunanda; S., Sowmya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Intrauterine fetal demise (IUFD) is an obstetric catastrophe which is immensely distressing to the pregnant women. Intrauterine fetal death refers to babies with no signs of life in utero. It is a significant indicator of maternal and perinatal health of the population. This study aims at assessing the incidence and possible maternal, fetal and placental factors predisposing to Intrauterine fetal death. Methods: This is a retrospective observational study conducted on pregnant women with Intrauterine fetal demise during study period of 1 year from June 1st 2023 to June 1st 2024 at MMCRI, Mysore. The data was collected from previous records of 170 IUFD cases from 6944 births. The parameters assessed were age, parity, gestational age and the probable etiology. Results: The most common maternal cause of IUFD was Hypertensive disorders (31.7%) followed by Diabetes (15.2%) and idiopathic category (15.2%). The most common fetal cause was IUGR (8.2%) and most common placental cause was placenta previa (11.7%). Conclusion: In our study, the incidence of IUFD was found to be 2.4% and the most common attributed cause was hypertensive disorders of pregnancy, gestational diabetes which were mostly preventable by early referrals, prompt diagnosis and timely interventions.